2020
DOI: 10.2166/wcc.2020.238
|View full text |Cite
|
Sign up to set email alerts
|

Coupled application of R and WetSpa models for assessment of climate change impact on streamflow of Werie Catchment, Tigray, Ethiopia

Abstract: This research assesses the streamflow response of Werie River to climate change. Baseline (1980–2009) climate data of precipitation, maximum and minimum temperature were analyzed using delta based statistical downscaling approach in R software packages to predict future 90 years (2010–2099) periods under two emission scenarios of Representative Concentration Pathways (RCP) 4.5 and RCP 8.5, indicating medium and extremely high emission scenarios respectively. Generated future climate variables indicate Werie wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…The result obtained under all the scenarios considered in this study have shown increasing trend. This result agrees with different studies made by other researchers in Ethiopian catchments (IPCC 2014, Asnake et al , 2020; Gashaw et al , 2020; Selam et al , 2020).…”
Section: Resultssupporting
confidence: 93%
“…The result obtained under all the scenarios considered in this study have shown increasing trend. This result agrees with different studies made by other researchers in Ethiopian catchments (IPCC 2014, Asnake et al , 2020; Gashaw et al , 2020; Selam et al , 2020).…”
Section: Resultssupporting
confidence: 93%
“…The study results suggest that Tmin will likely follow the same pattern for both scenarios. Although unexpected, previous studies have also found similar results [21,53]. Global warming is a result of increased greenhouse gases (GHG) in the atmosphere.…”
Section: Projected Trend Of Average Maximum and Minimum Air Temperatu...mentioning
confidence: 71%
“…For regions with no snowing, each of these parameters can be set to −1.0 [ 39 ]. Similar adjustments were made by Kidanemariam et al (2021) presuming that no significant snow formation occurred in the targeted basin [ 43 ]. The ability to adjust slightly sensitive or insensitive parameters comes as an added advantage when narrowing down the feasible parameter range [ 44 ].…”
Section: Methodsmentioning
confidence: 77%